Smoothing food price trends in Nigeria: Political economy issues and policy vistas - Aderibigbe S. Olomola (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
This study reviews the political economy issues surrounding the 2008 food crisis in Nigeria; the lessons learned from management of the crisis; analyses the performance of policies aimed at stabilizing prices; and proffers policy measures for preventing future occurrence. The study finds that the country has not been under any threat of food crisis since the 2008 episode. Since 2011, medium-term policies and strategies are redesigned and entrenched as major components of the agricultural transformation agenda. The implementation of the agenda has led to an increase in domestic food production, reduction in food imports, and stabilization of food prices.
Keywords: E31; O13; P16; Q18; 330; food prices; Nigeria; political economy; policy